A historical specimen of enantiornithine bird from the Early Cretaceous of Mongolia representing a new taxon with a specialized neck morphology. (2nd April 2016) - Zelenkov, Nikita V.; Averianov, Alexander O.
Abstract : We describe Holbotia ponomarenkoi gen. et sp. nov., the first articulated specimen of an enantiornithine bird from Mongolia, unearthed in 1977 from Early Cretaceous deposits and formerly thought to be a pterosaur. The specimen shows a series of morphological details that are either unique to the new taxon or very poorly known for Enantiornithes. A previously unobserved specialized cervical morphology, the development of a crest on the caudal surface of the distal tibia, and the presence of unusually widely spaced small teeth in the lower jaw are unique features of Holbotia . The results of a phylogenetic analysis indicate that Holbotia is more closely related to the Late Cretaceous edentulous Gobipteryx than to the Early Cretaceous enantiornithines with reduced dentition (Longipterygidae), which implies a different evolutionary pathway for the loss of teeth in Enantiornithes, as compared with Ornithuromorpha. The only preserved cervical vertebra of Holbotia ponomarenkoi displays partly ventrally facing prezygapophyseal articular surfaces, otherwise found only in the darters (Anhingidae), which implies an unusually increased degree of neck mobility. Morphology of the palate, described in detail for an Early Cretaceous enantiornithine bird for the first time, is roughly similar to that of Archaeopteryx and non-avian paravians. It shows that the evolution of specialized rostral morphology in Early Cretaceous enantiornithines was possible with retention of the primitive palatal structure, in contrast to modern birds (Neornithes), where the diversification of skull types was coupled with the evolution of several types of palate. http://zoobank.org/urn:lsid:zoobank.org:pub:42845FFC-4E4B-4FEE-9D76-0B5A7D9E127B